IMPACT OF FALSE DV COMPLAINTS ON TIMELY JUSTICE FOR GENUINE VICTIMS: A STUDY OF CASE BACKLOGS IN FAMILY COURTS - VATAN ,SH DR. SURENDER KALYAN (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Domestic violence (DV) laws were enacted to protect vulnerableindividuals, especially women, from abuse within domestic relationships. In India, the Protection of Women from Domestic Violence Act, 2005 (PWDVA) serves as a major legal mechanism for ensuring protection,